Clinical efficacy of 1% metformin gel around conventionally placed dental implants: A 9-month follow-up study - Govardhani Krishnakumar; Sitamahalakshmi Koppu; Jampani Narendra Dev; Vajra Madhuri Songa; Lahari Buggapati; Radhika Mandrachalam (Wolters Kluwer Medknow Publications, 2023)
Aim: The study aimed to compare the clinical and radiographic outcomes of bone volume, density, and crestal bone levels in conventionally placed dental implants with and without local application of 1% metformin (MF) gel using cone-beam computed tomography (CBCT) at 9 months. Materials and Methods: Twenty implants were placed in 18 individuals, randomly divided into 2 groups where Group A received a local application of 1% MF gel along with implant placement. In contrast, Group B received implant placement alone. After thorough clinical examination and preoperative CBCTs, implants were placed under aseptic conditions. Patients were recalled at 3 and 9 months after surgery. Implants were functionally loaded by the end of 3rd month. Soft-tissue parameters such as modified plaque index and modified sulcular bleeding index were recorded along with CBCT evaluation to assess the crestal bone loss, bone density measurement, and bone volume, postoperatively. Fisher's extract test, independent and paired t-test, and Bonferroni analysis were used to determine statistical significance with P ≤ 0.05. Results: There was no discernible difference between the groups regarding soft-tissue parameters, bone density, and crestal bone levels. However, comparing bone volume between the test and control groups at 9 months was statistically significant. The test group with 1% MF gel showed increased bone volume around the implant. Conclusion: The data obtained were strong enough to suggest that 1% MF gel administered locally can increase peri-implant bone volume, possibly due to its additional property favoring osteoblastic stimulation and proliferation.